Short Communication: Determination of crude oil degradation efficiency of biofilm producing bacteria isolated from oil contaminated site (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Khoo DH, Shivanand P, Taha H. 2022. Short Communication: Determination of crude oil degradation efficiency of biofilm producing bacteria isolated from oil contaminated site. Biodiversitas 23: 4138-4143. Microbes have gained much attention for their application in the bioremediation of petroleum contaminated areas, and biofilm producing bacteria are considered potential candidates for this purpose. The aim of this study was to screen six oil degrading bacterial strains for their ability to form biofilm, and to measure the crude oil degradation efficiency of selected strains. It was found that only two strains, Micrococcus sp. UBDBH15 and Pseudomonas sp. UBDBH26 were categorized as strong biofilm producers, with the latter showing the highest amount of biofilm formed. Under the conditions tested, Pseudomonas sp. UBDBH26 was also found to have the highest degradation rate (0.0047 g/day) with a significant degradation of 7.07 ± 3.02 and 11.38 ± 2.93 % of crude oil after 7 and 14 days respectively. Micrococcus sp. UBDBH15 had a lower rate of degradation (0.0033 g/day), resulting in a non-significant degradation. However, in comparison with a non-biofilm producer, Enterobacter sp. UBDBH06, this study suggested that biofilm might enhance the degradation of oil, but further studies are needed to confirm this assumption.
Keywords: Bacteria, biodegradation, biofilm, bioremediation, petroleum